The Use of Language Style by Native and Non-Native Speakers of English in the Ellen Show - Ade Dwi Cahyanti; Rudi Hartono (Universitas Negeri Semarang, 2021)
Language style can help the speaker which includes native and non-native speakers of English to communicate with the interlocutor in a suitable context. Here, the speaker has to consider the use of language style based on the place and person who talk to. By applying language style properly, the speaker can avoid social consequences. This research aims to investigate the language style used by the native and non-native speaker of English in The Ellen Show. This research was qualitative research. Furthermore, the source of data was three native speakers of English and three non-native speakers of English as the guests in the talk show program namely The Ellen Show. In analyzing the data, the researcher employed the language style suggested by Martin Joos (1967). There are five types of language style that focus on the level of formality such as frozen style, formal style, consultative style, casual style, and intimate style. The findings revealed all types of language styles occurred on the utterances of both native and non-native speakers of English in The Ellen Show. The native speakers of English used two frozen styles, two formal styles, sixteen consultative styles, nineteen casual styles, and one intimate style in their utterances. Moreover, the non-native speakers of English used six formal styles, twenty-seven consultative styles, and thirteen casual styles in their utterances. Additionally, all of the user of communication both native and non-native speakers of English used language style in their utterances. However, the speaker applied it relating to the relation with the interlocutor and the occasion.